The Concept of the Political - Morgenthau, Hans J. author. aut Link
X, 164 p.
Keywords: A growing interest in the oeuvre of Hans J. Morgenthau and in re-readings of 'classical realism' increases the significance of his European, pre-emigration writings in order to understand the work of one of the founding figures of IR. This book is the first English translation of Morgenthau's French monograph La notion du politique from 1933 (translated by Maeva Vidal).